THE INFLUENCE OF INFORMATION TECHNOLOGIES ON THE HUMAN FACTOR WITHIN AN ORGNANIZATION (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2005)
The article discusses a number of important changes of influence of information technologies on human factor within the organization. The focus of the article is on human factor and IT using problem. According to the theoretical and empirical material of IT influence on human factor, aspects of information technology are analyzed.